ANALISIS BIAYA MEDIS LANGSUNG DAN TARIF INA-CBG’s PASIEN DIABETES MELITUS TIDAK TERGANTUNG INSULIN DI RSUD ANUTAPURA PALU - Rinaldhi Tandah, Muhamad; Rhaudatul Janna, Rischa; Mallisa, Twulyenna; Khusnul Diana (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Diabetes mellitus is a long-term disease with an increasing prevalence. Diabetes mellitus is one of the main causes of human morbidity and death and has a significant impact on health financing. Indonesia itself has implemented a national health insurance program that prioritizes effectiveness and cost efficiency. This study aims to determine the average direct medical costs, INA-CBG's rates, the suitability of direct medical costs and INA-CBG's as well as the influence of treatment class, severity, number of secondary diagnoses, and length of stay on the direct medical costs of diabetes mellitus patients at Anutapura Hospital Palu. This research is a descriptive observational study with retrospective data collection from medical records and files detailing patient care costs at Anutapura Hospital Palu in 2020 from the hospital's perspective. The sample used was BPJS inpatients with a primary diagnosis of type 2 diabetes or non-insulin dependent diabetes mellitus (DMTTI) who met the inclusion and exclusion criteria, totaling 132 patients. Data were analyzed descriptively and to see the influence of variables on total costs, the Independent sample t-test and Mann-Whitney test were used. The research results show that the average direct medical costs are IDR 2,751,449, the average INA-CBG's rate is IDR 4,505,508, so there is a mismatch between direct medical costs and INA CBG's. There is a significant influence partially or simultaneously and in a positive direction from the variables treatment class, severity, number of secondary diagnoses, and length of stay on direct medical costs.